Design with nature and eco-city design. Issue 1 (16th December 2020) - Wu, Yegang; Swain, Robert E.; Jiang, Nan; Qiao, Mengying; Wang, Haihua; Bai, Jialin; Zhou, Xi; Sun, Xuefeng; Xu, Jing; Xu, Meng; Hu, Chen; Xing, Yimin; et al.
ABSTRACT: Designing with Nature is an approach linking design and ecology, which focuses on living with nature, caring for nature, and aiming for a sustainable society. China has made eco-city development, eco-restoration, and eco-civilization its legislative priority and its national strategy, investing a US$618 billion in a 5-year period from 2011–2015 that could reach as high as US$1, 124 billion dollars in the period of 2016–2020. "Designing with nature" also means that we must, as we are dealing with resources, consider and understand all the impacting factors and ecosystem capacities. China's biggest challenge has been to restore water quality, aquatic ecosystems, and landscape patterns. Alongside its natural resources and eco-city development, China possesses a solar energy capacity higher than that of any other country in the world, reaching 174 gigawatts by 2018. Solar power is now cheaper than fossil fuels in hundreds of Chinese cities. In this review, we affirm that the nature-driven design put forth by McHarg's Design with Nature has withstood the test of time, and we aim to renew interest in McHarg's ideas by arguing for a design of Chinese cities that is, in keeping with Design with Nature, future-oriented, nature-oriented, and sustainability-oriented.